2018
DOI: 10.3390/ma11020251
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Magnetic Properties at the Nanometer Scale in Continuously Graded Ferromagnets

Abstract: Ferromagnetic alloy materials with designed composition depth profiles provide an efficient route for the control of magnetism at the nanometer length scale. In this regard, cobalt-chromium and cobalt-ruthenium alloys constitute powerful model systems. They exhibit easy-to-tune magnetic properties such as saturation magnetization MS and Curie temperature TC while preserving their crystalline structure over a wide composition range. In order to demonstrate this materials design potential, we have grown a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…We have previously shown that composition grading of CoRu can be used to create multilayer samples with nanoscale modulation of the saturation magnetization 9 . In this work, we consider the temperature dependent magnetic properties of this type of sample and the corresponding magnetic depth profile evolution.…”
Section: Sample Preparationmentioning
confidence: 99%
“…We have previously shown that composition grading of CoRu can be used to create multilayer samples with nanoscale modulation of the saturation magnetization 9 . In this work, we consider the temperature dependent magnetic properties of this type of sample and the corresponding magnetic depth profile evolution.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Ferromagnetic thin films with graded properties have been experimentally fabricated by alloying magnetic and non-magnetic materials via co-sputtering. The desired depth-dependent composition can be achieved by tuning the relative rate of deposition of each material during growth [40][41][42][43][44][45]. The above mentioned technique is nowadays a well-established strategy to obtain depth-dependent magnetic anisotropy within a film (exchange spring systems), motivated by the demand of the magnetic recording industry of bitcells with a combination of low coercivity, to facilitate data writing, while ensuring good thermal stability [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…The above mentioned technique is nowadays a well-established strategy to obtain depth-dependent magnetic anisotropy within a film (exchange spring systems), motivated by the demand of the magnetic recording industry of bitcells with a combination of low coercivity, to facilitate data writing, while ensuring good thermal stability [46][47][48]. Besides anisotropy, the Curie temperature and saturation magnetization can be controlled as a function of depth introducing different concentrations of Cr or Ru dopants, allowing to manipulate the magnetization reversal process [45]. However, the influence of a continuous variation of the magnetic properties (along the film thickness) on the SW spectra and the discussion about the nature of the modes have not been addressed so far, and constitutes the main topic investigated here.…”
Section: Introductionmentioning
confidence: 99%
“…For our experimental approach, it is most suitable to select a specific thin film material system that can be epitaxially fabricated with in-plane uniaxial magnetocrystalline anisotropy to have negligible demagnetizing effects. This ensures that our samples exhibit very simple magnetization reversal behavior, which is dominated by magnetization rotation and switching, and produces uniform magnetization states for nearly all external field strengths and orientations [40,[45][46][47][48]. As a random alloy, CoRu adopts the hexagonal close packed crystal structure over a wide Ru dopant range and exhibits a magnetic easy axis (EA) behavior along its c-axis.…”
Section: Materials Design and Structural Characterizationmentioning
confidence: 99%
“…As a random alloy, CoRu adopts the hexagonal close packed crystal structure over a wide Ru dopant range and exhibits a magnetic easy axis (EA) behavior along its c-axis. Thus, we have utilized CoRu alloys for our films [45][46][47][48], whose layer structure is shown in figure 1(a). Ag and Cr underlayers were first deposited to promote highly oriented (211) Cr 0.804 Ru 0.196 layers, which in turn served as a template for the epitaxial growth of 60 nm thick (10 10) Co 1−x(z) Ru x(z) compositionally modulated layers.…”
Section: Materials Design and Structural Characterizationmentioning
confidence: 99%